Synthesis and characterization of cellobiose-derived oligosaccharides with Bifidogenic activity by glucansucrase E81 - Ispirli, Humeyra; Bowman, Michael J.; Skory, Christopher D.; Dertli, Enes (ELSEVIER, 2021)
Cellobiose-derived oligosaccharides were produced from acceptor reactions with glucansucrase E81 and their prebiotic potentials were determined in this study. The major product was a mixture of trisaccharides formed by the addition of an alpha-linked glucose to cellobiose at either the 2-O position of the reducing end (86%) glucose or the 6-O position of the non-reducing end glucose (11%) demonstrated by NMR spectroscopy and LC-MS-LTQ analysis. The purified DP 3 cellobiose-derived oligosaccharides were then tested for in vitro human gastric juice and alpha-amylase digestion and no digestion was observed during the 6 h digestion period. Importantly, DP 3 cellobiose-derived oligosaccharides promoted the growth of Bifidobacteria at high levels demonstrating a Bifidogenic effect and a mild level of proliferation was observed for Lactobacilli suggesting the prebiotic roles of cellobiose-derived oligosaccharides.
Keywords: Glucansucrase; Prebiotic oligosaccharides; Cellobiose-derived oligosaccharides; STRUCTURAL-CHARACTERIZATION; GALACTO-OLIGOSACCHARIDES; ACCEPTOR REACTIONS; ALTERNANSUCRASE; LACTOSE; SUCROSE; GROWTH; DEXTRANSUCRASE; TRISACCHARIDE; FERMENTATION; Food Science & Technology